Thermal ablation for the treatment of malignant thyroid nodules: present and future - Yan Hu; Wei Zhou; Shangyan Xu; Wanru Jia; Guiping Zhang; Yuan Cao; Qianru Zhang; Lu Zhang; Weiwei Zhan (International Journal of Hyperthermia)
As the utilization of high-resolution imaging modalities, such as ultrasound, becomes increasingly prevalent, there has been a swift rise in the detection rates of malignant thyroid nodules (MTC). Surgery remains the cornerstone of standard treatment for these nodules. However, the advent and evolution of thermal ablation (TA) techniques, encompassing radiofrequency ablation, laser ablation, and microwave ablation, have emerged as a novel therapeutic avenue for patients with MTC, particularly for those deemed unsuitable for surgery due to high risks or for those who refuse surgery. Presently, TA has been validated as an efficacious and safe intervention for both benign thyroid nodules and a subset of MTC. An expanding body of research has been dedicated to broadening the applicability of TA, initially from recurrent thyroid cancer and lymph nodes to now encompass isolated papillary thyroid microcarcinomas (PTMC) alongside a comprehensive exploration into the expanded parameters such as size, number, and location of PTMC, and its applicability in other types of thyroid cancer. This review provides a detailed synthesis of the clinical evidence about the use of TA in the management of MTC, as endorsed by current guidelines. It further delves into the ongoing research efforts aimed at extending its indications and discusses the prospective implications and challenges of integrating TA into the clinical management paradigms for MTC.